2011
DOI: 10.1007/s00345-011-0652-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parathyroid hormone on hypogonadism induced bone loss of proximal femur of orchiectomized rat

Abstract: PurposeManagement of hypogonadism-induced osteoporosis in elderly men is still a challenge. We investigated the short-term effects of parathyroid hormone (PTH) treatments on strength, micro-architecture, and mineral density of trochanteric region of orchiectomized rat femur.MethodsEight-month-old male Sprague–Dawley rats (n = 44) were divided into two groups: (1) orchiectomized (ORX) and (2) sham group. Twelve weeks after orchiectomy, half of the orchiectomized animals were treated with daily subcutaneously in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Recent study showed that PTH administration improved bone healing in both healthy and ovariectomy-induced osteopenic rats regardless of application frequency (7, 5 times per week or every other day) [14]. Part of the present study has been published previously [15,16]. It was shown, that in aged males the effect of PTH on bone healing was less when it was applied with less frequency (every day vs. every other day) [15].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Recent study showed that PTH administration improved bone healing in both healthy and ovariectomy-induced osteopenic rats regardless of application frequency (7, 5 times per week or every other day) [14]. Part of the present study has been published previously [15,16]. It was shown, that in aged males the effect of PTH on bone healing was less when it was applied with less frequency (every day vs. every other day) [15].…”
Section: Introductionsupporting
confidence: 53%
“…It was shown, that in aged males the effect of PTH on bone healing was less when it was applied with less frequency (every day vs. every other day) [15]. The proximal femur responded to PTH treatments positively showing improved biomechanical properties, mineral content and trabecular bone parameters [16]. Thus, PTH improved tibia healing and reversed structural impairment in femur in male rats.…”
Section: Introductionmentioning
confidence: 86%
“…The ovariectomized (OVX) rat is the most appropriate experimental model for postmenopausal bone loss that faithfully reproduces the changes observed in human subjects and has the added benefit that the effects are detectable only a few months after gonadectomy [14,22]. There are many similarities between the human and rat femur, both at the microstructural and macrostructural levels [23,24]. There are many similarities between the human and rat femur, both at the microstructural and macrostructural levels [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The femur is one of the most important skeletal sites in postmenopausal osteoporosis. For these reasons, this skeletal site has gained special meaning and great importance in osteoporosis studies [24]. For these reasons, this skeletal site has gained special meaning and great importance in osteoporosis studies [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that both the osteoporosis-related morbidity and mortality in men actually were higher than those in women in later life [ 1 , 2 ]. The increased risk of fractures is closely associated with the decline of testosterone production, which causes a high turnover bone loss from cancellous bone sites [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%